Comparative analysis of two next-generation sequencing platforms for analysis of antimicrobial resistance genes. (December 2022) - Soni, Twinkle; Pandit, Ramesh; Blake, Damer; Joshi, Chaitanya; Joshi, Madhvi
ABSTRACT: Objectives: The use of antibiotics in human medicine and livestock production has contributed to the widespread occurrence of Antimicrobial Resistance (AMR). Recognizing the relevance of AMR to human and livestock health, it is important to assess the occurrence of genetic determinants of resistance in medical, veterinary, and public health settings in order to understand risks of transmission and treatment failure. Advances in next-generation sequencing technologies have had a significant impact on research in microbial genetics and microbiome analyses. The aim of the present study was to compare the Illumina MiSeq and Ion Torrent S5 Plus sequencing platforms for the analysis of AMR genes in a veterinary/public health setting. Methods: All samples were processed in parallel for the two sequencing technologies, subsequently following a common bioinformatics workflow to define the occurrence and abundance of AMR gene sequences. The Comprehensive Antibiotic Resistance Database (CARD), QIAGEN Microbial Insight - Antimicrobial Resistance, Antimicrobial resistance database, and Comprehensive Antibiotic Resistance Database developed by CLC bio (CARD-CLC) databases were compared for analysis, with the most genes identified using CARD. Results: Drawing on these results, we described an end-to-end workflow for the analysis of AMR genes a using advances in next-generation sequencing. No statistically significant differences were observed among any other genes except the tet-(40) gene between two sequencing platforms, which may be due to the short amplicon length. Conclusions: Irrespective of sequencing chemistry and platform used, comparative analysis of AMR genes and candidate host organism suggest that the Illumina MiSeq and Ion Torrent platforms performed almost equally. Regardless of sequencing platform, the results were closely comparable with minor differences.